Table of Content - -, (Journal of medical and pharmaceutical sciences, 2023)
Table of Content1. International Alliance of Urolithiasis (IAU) Guideline on percutaneous nephrolithotomyDr. Wissam Khalid Kamal, Dr. Mahmoud Abdulaziz Alakraa2. Perception of School Nurses in Saudi ArabiaDr. Hala Mohammed Yasin, Dr. Pilar Isla Pera, Dr. Alaa Mujallad, Dr. Carmen López Matheu3. A community-based study of prevalence and risk factor for “Schistosoma haematobium”  in Two Endemic Districts of Taiz, YemenDr. Abdullnasser Ahmed Al-Kabab, Dr. Einas Ibrahim El-Sheikh, Dr. Abdulla Abdu Al-Mikhlafy4. The association between metabolic syndrome and hypothyroidism in school-aged obese childrenDr. Zeina Fawaz Alkilany, Prof. Ahmad Chreitah, Dr. Youssef Zreik5. Knowledge, Attitude and Practice of Omani Women on Breast Self-Examination in Oman: A Grounded TheoryDr. Zalikha Khamis Darwish Al-Marzouqi, Nawal Said Al-Surihi6. The Effect of Omega-3 Medication on Autistic Children in Riyadh, Saudi ArabiaDr. Maryam Alhassan Alnami, Dr. Maram Abdulmohsen Alswayegh
Keywords: Journal of Medical and Pharmaceutical Sciences